Near-Peer Teaching Outreach Programs to Increase Minority Physician Recruitment - Linderman, Wendy F.; Apostolopoulos, Nicholas; Gopal, Anand D.; Encandela, John A.; Teng, Christopher C.; Nwanyanwu, Kristen H.; Forster, Susan H. (Journal of Academic Ophthalmology, 2018)
Problem Health disparities among racial and ethnic groups exist in the United States despite improvements in health status and access to care. These inequalities may be reduced by increasing minority physician recruitment; however, how best to recruit these physicians remains unclear.Approach Near-peer teachers are not professionally trained, but have recently learned material that they themselves teach. Near-peer teaching in minority student outreach programs may be effective in increasing minority physician recruitment. The authors used a near-peer teaching model to promote interest in medicine, specifically ophthalmology, as a potential career path for both volunteer near-peer teachers and minority high school students participating in an educational outreach program. Twenty-one college and graduate-school near-peer teachers of various racial and ethnic backgrounds participated to teach 31 inner-city high school students. The program was evaluated using pre- and posttest surveys assessing students' knowledge about and interest in science, medicine, and ophthalmology; analysis used pairwise t-test comparisons. Qualitative responses and an end-of-training survey also assessed students' and near-peer teachers' satisfaction with the program and perceptions about medicine as a career.Outcomes Students' knowledge about and interest in medicine and ophthalmology increased significantly after participation. Near-peer teachers agreed that teaching in the program was beneficial to their careers and made it more likely that they would enter medicine and ophthalmology.Next Steps The authors will track the near-peer teachers' career paths and, in the next iteration, will increase the number of program days. This intervention may serve as a model for outreach for other specialties beyond ophthalmology.
Keywords: near-peer teaching; outreach; minority students; inner city; physician recruitment